DAMPAK KONVERSI TERHADAP TINGKAT EFESIENSI DI BANK ACEH - tuanku michael hakim lim; Amelisah Amelisah (Institut Binamadani Indonesia, 2022)
The purpose of this study is to analyze the Impact of Conversion on the Level of Efficiency at Bank Aceh. This study uses Bank Aceh Syariah data published on the official website of Bank Aceh 2010 to 2018. The results of data analysis using multiple regression methods using dummy variables to measure the policy of conversion to efficiency. The variables used are Conversion dummy and Third Party Funds (DPK), Non Performing Finance (NPF), and Finance to Deposit Ratio (FDR). The results showed that the conversion dummy variable had an effect on efficiency, DPK had a negative and significant effect on efficiency, NPF had a positive and significant effect on efficiency while FDR had a negative and significant effect on efficiency.